Normative scores for the Timed Up & Go in a Spanish sample of community-dweller adults with preserved functionality - Pereiro, Arturo X. (Aten Primaria, 2021)
Our aim was to calculate the ‘Timed Up & Go’ (TUG) normative scores in a Spanish sample composed of functional older adults. The TUG test provides a measure of global ambulation skills and its total score has been successfully related with functionality and other important health variables in older adults. Reliable norms are needed for adults 50 years and older that allow the early identification and intervention in motor disturbances. The study was carried out with adults from Galicia and Valencia living in the community. A total of 314 Spanish community-living participants, aged from 50 to 90 years and functionality preserved were assessed through the implementation of a cross-sectional design. Health, comorbidity, physical activity, cognitive status, functionality measures and TUG test scores were obtained. TUG scores were successfully predicted by age and gender, and significantly correlated with cognitive status and comorbidity. TUG norms were calculated by age-group for women and men. TUG normative scores were below 13 s and slightly lower in men. Normative scores for women and men were lower than those proposed in studies carried-out in our context. Our norms showed risk reference scores close to those obtained by meta-analytical procedures.